Minimal doses of hydroxyurea for sickle cell disease - C.S.P. Lima; V.R. Arruda; F.F. Costa; S.T.O. Saad (Brazilian Journal of Medical and Biological Research, 1997)
The use of hydroxyurea (HU) can improve the clinical course of sickle cell disease. However, several features of HU treatment remain unclear, including the predictability of drug response and determination of adequate doses, considering positive responses and minimal side effects. In order to identify adequate doses of HU for treatment of sickle cell disease, 10 patients, 8 with sickle cell anemia and 2 with Sß thalassemia (8SS, 2Sß), were studied for a period of 6 to 19 months in an open label dose escalation trial (10 to 20 mg kg-1 day-1). Hemoglobin (Hb), fetal hemoglobin (Hb F) and mean corpuscular volume (MCV) values and reticulocyte, neutrophil and platelet counts were performed every two weeks during the increase of the HU dose and every 4 weeks when the maximum HU dose was established. Reduction in the number of vasoocclusive episodes was also considered in order to evaluate the efficiency of the treatment. The final Hb and Hb F concentrations, and MCV values were significantly higher than the initial values, while the final reticulocyte and neutrophil counts were significantly lower. There was an improvement in the concentration of Hb (range: 0.7-2.0 g/dl) at 15 mg HU kg-1 day-1, but this concentration did not increase significantly when the HU dose was raised to 20 mg kg-1 day-1. The concentration of Hb F increased significantly (range: 1.0-18.1%) when 15 mg HU was used, and continued to increase when the dose was raised to 20 mg kg-1 day-1. The final MCV values increased 11-28 fl (femtoliters). However, reticulocyte (range: 51-205 x 109/l) and neutrophil counts (range: 9.5-1.3 x 109/l) obtained at this dose were significantly lower than those obtained with 15 mg kg-1 day-1. All patients reported a decrease in frequency or severity of vasoocclusive episodes. These results suggest that a hydroxyurea dose of 15 mg kg-1 day-1 seems to be adequate for treatment of sickle cell disease in view of the minimal side effects observed and the improvement in laboratory and clinical parameters.